Relationships between clinical features of neck pain and reaction and response times in individuals with chronic neck pain - Sittikraipong, Kawintra; Uthaikhup, Sureeporn (Journal of Associated Medical Sciences, 2019)
Background: Dysfunction of sensorimotor integration can influence the execution of the reaction time and motor task. Although evidence suggests the association of neck pain and sensorimotor dysfunction, relationship between clinical features of neck pain and reaction and response times is still unknown. Objectives: To examine the relationship between clinical features of neck pain and upper limb disability, and reaction and response times in individuals with chronic neck pain. Materials and methods: Fifty-six individuals with chronic neck pain aged between 18-59 years were recruited for the study. Clinical features included pain intensity using Visual Analogue Scale (VAS), pain duration, neck disability using Neck Disability Index-Thai version (NDI-TH), and upper limb disability using Disabilities of the Arm, Shoulder and Hand-Thai version (DASH-TH). Hand reaction and response times were assessed using hand-held electronic timer with a modified computer mouse and foot reaction and response times using a pedal switch. Pearson’s correlation coefficient was used to analyze the relationships between variables. Results: NDI-TH score was mildly correlated with hand and foot reaction and response times (r ranged from 0.29 and 0.32, p<0.05). DASH-TH score (8 items related to neck pain) was positively correlated with hand reaction and response times (r=0.26 and 0.34, respectively, p<0.05) but not with foot reaction and response times (p>0.05). There was no correlation between intensity and duration of neck pain and the hand and foot reaction and response times (p>0.05). Conclusion: There was a mild correlation between neck and upper limb disability and slower hand reaction and response times. The neck disability was mildly correlated with slower foot reaction and response times.